Manajemen Organisasi Dalam Meningkatkan Kedisiplinan Santri Di Pondok Pesantren Darussalam Dukuhwaluh Purwokerto - Evaliya Isni Alhidayah; Muh. Hanif (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2021)
This research aims to analyze organizational management in improving student discipline. This research method uses qualitative where the research is carried out based on literature or literature review and uses a qualitative approach to conduct field research by collecting data by observation, interviews and documentation. The subjects in this research were students at the Darussalam Islamic Boarding School. Meanwhile, the object is organizational management in instilling discipline in Darussalam Islamic Boarding School students. The data analysis used is qualitative descriptive analysis. From this research, it can be seen that organizational management with a future orientation and involving other management functions can improve the discipline of students in Islamic boarding schools. Management of student discipline in Islamic boarding schools requires the implementation of management functions to minimize violations and increase management effectiveness.